Evaluasi Penerapan Tahun Pertama Berlakunya Standar Audit (SA 701) Pengomunikasian Hal Audit Utama - Serinteg, I Made; Mita, Aria Farah (E-Jurnal Akuntansi, 2024)
Auditing Standards (SA) 701 in Indonesia are effective for the implementation of general audits of issuers' financial statements in the period starting January 1 2022. The research aims to evaluate the implementation of the first year of SA 701 coming into force. The research was conducted at KAP ABC, which is one of the KAPs in Indonesia. The data in this research uses primary data and secondary data. Primary data was obtained through semi-structured interviews, while secondary data was in the form of audit policies and procedures from KAP ABC. The research results show that KAP ABC is able to implement SA 701 well even though its international affiliate does not provide an audit methodology. The obstacles faced by KAP ABC in implementing SA 701 are communication with parties responsible for governance and management regarding main audit matters, as well as the formulation of paragraphs on main audit matters in the auditor's report. Regarding the implementation of the audit, there were no significant changes to the audit process, considering that the overall audit process carried out was still the same. Keywords: SA 701; Key Audit Matters; Auditor's Report